Comparison Between Treadmill and Bicycle Ergometer Exercises in Terms of Safety of Cardiopulmonary Exercise Testing in Patients With Coronary Heart Disease - Ren, Chuan; Zhu, Jingxian; Shen, Tao; Song, Yanxin; Tao, Liyuan; Xu, Shunlin; Zhao, Wei; Gao, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiopulmonary exercise testing (CPET) is used widely in the diagnosis, exercise therapy, and prognosis evaluation of patients with coronary heart disease (CHD). The current guideline for CPET does not provide any specific recommendations for cardiovascular (CV) safety on exercise stimulation mode, including bicycle ergometer, treadmill, and total body workout equipment. Objective The aim of this study was to explore the effects of different exercise stimulation modes on the occurrence of safety events during CPET in patients with CHD. Methods A total of 10,538 CPETs, including 5,674 performed using treadmill exercise and 4,864 performed using bicycle ergometer exercise at Peking University Third Hospital, were analyzed retrospectively. The incidences of CV events and serious adverse events during CPET were compared between the two exercise groups. Results Cardiovascular events in enrolled patients occurred during 355 CPETs (3.4%), including 2 cases of adverse events (0.019%), both in the treadmill group. The incidences of overall events [235 (4.1%) vs. 120 (2.5%), P < 0.001], premature ventricular contractions (PVCs) [121 (2.1%) vs. 63 (1.3%), P = 0.001], angina pectoris [45 (0.8%) vs. 5 (0.1%), P < 0.001], and ventricular tachycardia (VT) [32 (0.6%) vs. 14 (0.3%), P = 0.032] were significantly higher in the treadmill group compared with the bicycle ergometer group. No significant difference was observed in the incidence of bradyarrhythmia and atrial arrhythmia between the two groups. Logistic regression analysis showed that the occurrence of overall CV events (P < 0.001), PVCs (P = 0.007), angina pectoris (P < 0.001), and VT (P = 0.008) was independently associated with the stimulation method of treadmill exercise. In male subjects, the occurrence of overall CV events, PVCs, angina pectoris, and VT were independently associated with treadmill exercise, while only the overall CV events and angina pectoris were independently associated with treadmill exercise in female subjects. Conclusion In comparison with treadmill exercise, bicycle ergometer exercise appears to be a safer exercise stimulation mode for CPET in patients with CHD.